2020
DOI: 10.1177/1753425920901563
|View full text |Cite
|
Sign up to set email alerts
|

Role of microRNA-21 and microRNA-155 as biomarkers for bronchial asthma

Abstract: MicroRNA (miRNA)-21 and miRNA-155 are important regulators of gene expression of different immunological molecules. This study aimed to investigate the role of miRNA-21 and miRNA-155 as biomarkers in asthma by comparing their serum expression levels in asthmatic patients to those in healthy controls and correlating their levels with serum IL-4. The expression levels of miRNA-21 and miRNA-155 were evaluated by quantitative RT-PCR. Serum levels of IL-4 were determined using ELISA. Asthmatic patients showed signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 45 publications
1
26
0
1
Order By: Relevance
“…Elkashef et al. have reported the use of miR-21 and miR-155 as biomarkers in bronchial asthma ( 62 ). They showed that both miRNAs are higher in serum of individuals with eosinophilic asthma than healthy subjects.…”
Section: Mirnas In Lung Diseasesmentioning
confidence: 99%
“…Elkashef et al. have reported the use of miR-21 and miR-155 as biomarkers in bronchial asthma ( 62 ). They showed that both miRNAs are higher in serum of individuals with eosinophilic asthma than healthy subjects.…”
Section: Mirnas In Lung Diseasesmentioning
confidence: 99%
“…According to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) standard, 47 the standard literature selection process was conducted as shown in Figure 1 . We finally included 72 articles 21 , 22 , 25 31 , 48 …”
Section: Resultsmentioning
confidence: 99%
“…In particular, there were five publications 51 , 53 , 55 , 61 , 92 among the 72 articles with the data details required for quantitative diagnosis analysis for miRNAs in asthma ( Table 2 ). There is no threshold effect based on the analysis of Spearman (Spearman correlation = 0.5946) which means that the study effect size could be combined.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations